Fabrication and characterization of nanostructured titanium dioxide (TiO2) for optical sensor application / Siti Farhaniza Abd Samat - Abd Samat, Siti Farhaniza (2021)
Titanium dioxide, TiO2 or titania is one of metal oxide which is most abundant and well-known semiconductors used in developing the optoelectronics applications technologies. The method used in this research study is sol-gel dip coating technique where it is easy to handle. The usage of high technologies is rapidly growth in sensing where the fast response and low cost effective are currently need. However, there are many factors effected the thin film to obtain a nanocrystalline phase that can achieve a good sensing performance. So that, the TiO2 thin film has to undergo a few parameters during solution preparation and dip coating process. The deposition parameters involved are precursor molar concentration, number of dipping cycle, withdrawal speed, number of layers, and annealing temperature to determine the optimized sensing membrane for crystalline phases and fast response time. Based on the result, the crystalline phase state was obtained in anatase and rutile in one layer deposition and annealed at 450oC. However, the UV light response needs more energy to perform fast response and also short recovery time. Therefore, the doping process of aluminum (Al) with TiO2 thin film is needed. According to the results, TiO2/Al bilayer configuration shows superior sensing performance as opposed to TiO2 thin film itself. It was found that TiO2/Al bilayer films possess response time and recover time at 4.8ms and 6.6s upon illumination at (365 nm) with 10V respectively. Besides, the TiO2 sensing membrane was tested in sampling with a different number of used fried cooking oil. The response of TiO2 thin film as a sensing membrane at a narrow wavelength under UV light photo response showed that the transmittance degradation related to the highly used cooking oil. All of these results demonstrate that this high-quality photosensor can be a promising candidate as a low-cost UV photodetector for commercially recycled cooking oil sensor applications.